Ikhwan al-Muslimin and Political Movement : (A Study of Hasan al-Banna’s Thought) - Tahir, Gustia (Universitas Islam Negeri Alauddin, 2023)
The Muslim Brotherhood is a movement founded by Hasan al-Banna in 1928. The aim of this movement was originally to spread Islamic values. However, in its development, the teachings of the Muslim Brotherhood spread beyond Egypt and grew into a political movement with the aim of ending British colonial control and destroying all Western influence. The organization's goal is to establish a state governed by sharia law with the slogan